The Effect of Bounding Attachment in Maternal Postpartum Blues Madura Ethnic - Ristanti, Adenia Dwi; Masita, Elly Dwi (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Postpartum blues is a transient state of increased emotional reactivity experienced by half of postpartum mothers within one week after delivery. The purpose of this study was to determine the effectiveness of bounding attachment in postpartum blues mothers. This type of research is a descriptive analytic study with a cross sectional design. Sampling using the rule of thumb sampling technique, can be used as respondents using the screening questionnaire EPDS and PBQ questionnaire. There is a relationship between bounding attachment and postpartum blues with a P value of 0.29, so it can be assumed that the postpartum blues influences the bounding attachment. It is hoped that the results of this study will become a source of reference in the development of midwifery science to improve the quality of midwifery care, especially for maternal midwifery services with postpartum blues.